2009
DOI: 10.1080/00365520802400859
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized comparison of mechanical and electronic radial endoscopic ultrasound systems: Assessment of performance parameters and image quality

Abstract: Electronic EUS provided better quality images according to the examiner's subjective assessment. An objective advantage was faster identification of the distal CBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
11
1
1
Order By: Relevance
“…However, ER-EUS with color-Doppler and harmonic imaging is now available, and there is no comparative study of ER-EUS and EC-EUS. There were only a few reports that showed ER-EUS could provide better images than mechanical radial EUS [16,17]. Thus, it is unknown whether ER-EUS is equivalent or superior for the detection of pancreatic malignancy, compared with EC-EUS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, ER-EUS with color-Doppler and harmonic imaging is now available, and there is no comparative study of ER-EUS and EC-EUS. There were only a few reports that showed ER-EUS could provide better images than mechanical radial EUS [16,17]. Thus, it is unknown whether ER-EUS is equivalent or superior for the detection of pancreatic malignancy, compared with EC-EUS.…”
Section: Discussionmentioning
confidence: 94%
“…With recent advances of EUS technology, electronic radial echoendoscope with the ability of harmonic and color-Doppler imaging have been developed [15], and a few studies showed it could provide better quality images, compared with the mechanical radial echoendoscope in the diagnosis of pancreatic lesions [16,17]. Therefore, the diagnostic accuracy of radial EUS with electronic ultrasound system may be improved, and better than EC-EUS in the diagnosis of pancreatic malignancies.…”
Section: Introductionmentioning
confidence: 97%
“…1 point : Artifact is too strong, and on the inside is not understood. with a scanning range of 360 degrees was introduced, and Papanikolaou et al reported its excellent image quality in normal structures in the pancreas, common bile duct, gastric wall, and esophageal wall 21) . We wished to objectively evaluate the ER -ES not with normal structures but with lesions, 2) Lesion's echo 5 points : It is clear.…”
Section: Resultsmentioning
confidence: 99%
“…Papanikolaou et al reported the excellent image quality of the ER -ES with a scanning range of 360 degrees ; however, they used normal structures, not lesions 21) . Therefore, the aim of this study was to compare the ER -ES and MR -ES, each with a scanning range of 360 degrees, in the quality of EUS images of gastrointestinal tract and pancreaticobiliary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Papanicolau et al [12] examine image quality and performance and compare between of an electronic and a mechanical radial echoendoscope Electronic EUS provided better quality images according to the examiner's subjective assessment. EUS availability, accessibility and utilization among clinicians from different European countries were assessed.…”
mentioning
confidence: 99%